2021
DOI: 10.1017/s0025315421000515
|View full text |Cite
|
Sign up to set email alerts
|

Larval development of the Caribbean king crab Maguimithrax spinosissimus (Lamarck, 1818), the largest brachyuran in the western Atlantic (Crustacea: Decapoda: Majoidea)

Abstract: The complete larval development of the spider crab Maguimithrax spinosissimus (Lamarck, 1818) is re-described and illustrated in detail from laboratory-reared material. The development consisted of the typical pattern reported for the Majoidea, two zoeal stages and one megalopa. The complete larval development from hatching to first crab lasted 5–6 days at temperatures that ranged between 24–28 °C. Both zoeal stages of M. spinosissimus exhibited moderate reduction in the number of setae in the maxilla and maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Also, the use of the Caribbean king crab Maguimithrax spinosissimus named by local fishers as "monstruito" was reported, in at least three localities (Progreso, Dzilam de Bravo, and San Felipe). This is the largest brachyuran crab in the Western Atlantic, reaching a carapace length of up to 180 mm and weighing more than 3 kg (Turini et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use of the Caribbean king crab Maguimithrax spinosissimus named by local fishers as "monstruito" was reported, in at least three localities (Progreso, Dzilam de Bravo, and San Felipe). This is the largest brachyuran crab in the Western Atlantic, reaching a carapace length of up to 180 mm and weighing more than 3 kg (Turini et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies, one conducted on large patch reefs (44 to 96 m 2 ) and another on contiguous reefs, arrived at similar estimates of D. antillarum retention (23%-30%) after 267-365 days (Wynne, 2008;Pilnick et al, 2022b). Olmeda-Saldaña et al (2021) showed that for more antillarum when urchin densities were above 0.15 urchin/m 2 but observed no effect on macroalgae at urchin densities of 0.04 urchin/m 2 . Stachowicz and Hay (1999b) postulated that high site fidelity and predation risk are associated with a broad generalist diet and compensatory feeding in marine crabs.…”
Section: Urchinsmentioning
confidence: 99%